(untitled) (International Journal of Occupational Safety and Health, 2021)
Introduction: There are huge numbers of drilling platforms in the world and once the worker on those platforms meet with an accident, the situation could be very serious. The consequence of this could be environmental, economic and in some cases fatal. Middle East, being one of the oil rich regions hence some of the largest operator works here. Companies here own various types of jack up rigs ranging from old generation rigs to the latest cyber-rig. This paper addresses what oil rig workers have to say about their interaction with machines, and how Human Machine Interaction (HMI) in Offshore Drilling can be improved with design. Methods: A case study approach was undertaken The analysis in this paper draws on the interviews conducted with two different employees involved in operating the drilling operations conducted in the driller’s cabin of newly designed offshore rigs. A semi-structured approach was adopted, using themes identified through analysis of the preceding. The interviews were transcribed by the research team. Each interview was analyzed thematically with existing system and reported discrepancy Results: The study on Human Machine Interaction (HMI) and Human Factor regarding this has been conducted in the latest generation cyber rigs. There are many aspects of HMI and ergonomics but in this study a special concentration has been given to deal with the ergonomic standpoint and evaluates the drillers console controls. Conclusion: When comparison is done with the existing machinery, few modifications can be thought of for better human machine interaction. A better human machine interaction system will ensure a more productive environment for the oil-rig workers.